EGFR and MEK Blockade in Triple Negative Breast Cancer Cells. Issue 12 (8th October 2015) - Maiello, Monica Rosaria; D'Alessio, Amelia; Bevilacqua, Simona; Gallo, Marianna; Normanno, Nicola; De Luca, Antonella
<x xml:space="preserve">Abstract</x> Although evidence suggests that the RAF/MEK/ERK pathway plays an important role in triple negative breast cancer (TNBC), resistance to MEK inhibitors has been observed in TNBC cells. Different mechanisms have been hypothesized to be involved in this phenomenon, including receptor tyrosine kinase‐dependent activation of the PI3K/AKT pathway. In this study, we analyzed the effects of the MEK1/2 inhibitor selumetinib in combination with the epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor gefitinib in a panel of TNBC cell lines that showed different levels of sensitivity to single‐agent selumetinib: SUM‐149 and MDA‐MB‐231 cells resulted to be sensitive, whereas SUM‐159, MDA‐MB‐468 and HCC70 cells were relatively resistant to the drug. Treatment of TNBC cells with selumetinib produced an increase of the phosphorylation of the EGFR both in selumetinib‐sensitive SUM‐149, MDA‐MB‐231 and in selumetinib‐resistant MDA‐MB‐468 TNBC cells. The combination of selumetinib and gefitinib resulted in a synergistic growth inhibitory effect in all the TNBC cell lines, although the IC50 was not reached in SUM‐159 and MDA‐MB‐468 cells. This effect was associated with an almost complete suppression of ERK1/2 activation and a reduction of selumetinib‐induced AKT phosphorylation. In addition, in selumetinib‐sensitive TNBC cells the combination of selumetinib and gefitinib induced a significant G0/G1 cell cycle arrest and apoptosis. Taken together, our data demonstrated that blockade of the EGFR might efficiently increase the antitumor activity of selumetinib in a subgroup of TNBC and that this phenomenon might be related to the effects of such combination on both ERK1/2 and AKT activation. J. Cell. Biochem. 116: 2778–2785, 2015. © 2015 Wiley Periodicals, Inc.